PERTUMBUHAN DAN PRODUKSI JAGUNG ( Zea may s L. ) PADA BERBAGAI METODE PENGENDALIAN GULMA - Norman Swasco Simanjuntak; Edison Purba; Jonatan Ginting (Jurnal Agroekoteknologi, 2014)
The presence of weeds in the cultivation of maize PRG C7 tolerant to glyphosate herbicide face theproblem of decline in maize production . The spraying of glyphosate herbicide can suppress weeds ,and is expected to increase the growth and production of maize in cultivation . Research conductedat Balai Benih Induk Tanaman Palawija crop field , Tanjung Selamat , Kecamatan sunggal,, NorthSumatra on March-July 2013, using a randomized block design (RBD ) with four types of nonfactorialmethod of weed control treatments and 4 replications . The parameters measured wereplant height , number of leaves , leaf length , leaf width , stem diameter , high productive cob,number of productive cob , cob length , cob diameter , cob weight klobot , klobot ear length , earweight without klobot , number of seeds per cob shelled , shelledgrain weight per ear, dry weight of 100 seeds,water content. The results showed that theeffect of glyphosate herbicide spraying is not real stem diameter and dry weight of 100 seeds butsignificant effect on other parameters.________________________________________________________________________________Keywords: product of genetic engineering, tolerant of glyphosate , glyphosate , weed , corn hybrids.